Translational medicine in abdominal military field surgery: from innovations to standards of care for abdominal gunshot wounds - V. A. Syusyura; R. I. Plishchuk; M. M. Magomedov; A. V. Pirogov; A. N. Kazantsev (Translational Medicine, 2026)
The high mortality rate of abdominal gunshot wounds (15–60 %), rising antibiotic resistance, and the need for accelerated innovation necessitate a systematic analysis of current approaches to diagnostics, surgical tactics, and translational medicine in military field surgery. The objective of this review is to develop a comprehensive scientific and practical paradigm for abdominal military field surgery that integrates epistemological, translational, and prognostic aspects. The methodology included searching the Russian Science Citation Index (RSCI), PubMed, Google Scholar, and CyberLeninka databases for the period 2023–2026, followed by narrative data synthesis. Thirty-six sources were analyzed, including national guidelines, original studies, clinical cases, and reviews. It was found that shrapnel and mine blast wounds predominate among abdominal gunshot wounds (65 %), with combined injuries occurring in 70 % of cases. Peritonitis is characterized by a polymicrobial landscape (80–85 %) with a high rate of multidrug resistance (30–60 %). Traumatic pancreatitis develops in 65 % of patients with direct pancreatic injury. Vacuum-assisted laparostomy reduces mortality from 45 % to 28 %. The FAST protocol reduces preoperative preparation time from 45 to 18 minutes. The translational model (stages T1–T4) enabled the introduction of vacuum-assisted laparostomy/vacuum-assisted laparostomy and endovideosurgical technologies into clinical guidelines within 3–5 years, confirming the high efficacy of the translational approach in extreme conditions. Conclusion. Translational medicine is an effective tool for accelerating the implementation of innovations in abdominal military field surgery; Vacuum-assisted technologies, artificial intelligence, and bioengineered methods for closure of abdominal wall defects remain priority areas.